Comprehensive characterization of hydrothermal liquefaction products obtained from woody biomass under various alkali catalyst concentrations. Issue 13 (7th June 2019) - Hwang, Hyewon; Lee, Jae Hoon; Choi, In-Gyu; Choi, Joon Weon
ABSTRACT: Hydrothermal liquefaction (HTL) of lignocellulosic biomass has been widely investigated for the production of renewable and alternative bio-crude oil. In this study, catalytic hydrothermal processing of two biomasses (larch and Mongolian oak) was performed using different K2 CO3 concentrations (0, 0.1, 0.5, 1.0 wt% of solvent) to improve fuel yield and properties. HTL oil, hydrochar, water-soluble fraction (WSF) and gas were characterized, and carbon balance was investigated. As a result, the maximum yield of HTL oil, 27.7 wt% (Mongolian oak) and 25.7 wt% (larch), and the highest carbon conversion ratio was obtained with 0.5 wt% of catalyst. The high catalyst concentration also resulted in an increase in higher heating values up to 31.9 MJ/kg. In addition, the amount of organic compounds in HTL oil also increased, specifically for lignin-derived compounds including catechol and hydroquinone which can be derived from secondary hydrolysis of lignin. On the other hand, formation of hydrochar was suppressed with the addition of alkali catalyst and the yield dramatically decreased from 30.7–40.8 wt.% to 20.0–21.8 wt.%. Furthermore, it was revealed that WSF had low organic carbon content less than 3.4% and high potassium content mostly derived from alkali catalyst, indicating that it may be reusable with simple purification. This work suggests that the addition of the proper amount of alkali catalyst can improve the production efficiency and quality of bio-crude oil, and another potential of WSF to be recyclable in further work.